2021
DOI: 10.1093/ehjci/jeab043
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial work in Stage 1 and 2 hypertensive patients

Abstract: Aims Myocardial work (MW) is a novel parameter that can be used in a clinical setting to assess left ventricular (LV) pressures and deformation. We sought to distinguish patterns of global MW index in hypertensive vs. non-hypertensive patients and to look at differences between categories of hypertension. Methods and results Sixty-five hypertensive patients (mean age 65 ± 13 years; 30 male) and 15 controls (mean age 38 ± 12 y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
36
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 17 publications
4
36
1
1
Order By: Relevance
“…25 The added clinical value of LV MW has been demonstrated in patients with hypertension or in aiding the prognostic stratification in patients with cardiac amyloidosis and ST-segment elevation myocardial infarction. 32,33 Furthermore, in the HFpEF setting, Przewlocka-Kosmala et al demonstrated that GCW is a better determinant of exercise capacity than GLS and that improvement in functional capacity during follow-up is associated with increment of GCW. 34 Using longitudinal MW analyses, the current study is the first to point out at the role of MW in the risk stratification of HFpEF patients and its association with clinical outcomes.…”
Section: Myocardial Work and Clinical Implications In Heart Failure W...mentioning
confidence: 99%
“…25 The added clinical value of LV MW has been demonstrated in patients with hypertension or in aiding the prognostic stratification in patients with cardiac amyloidosis and ST-segment elevation myocardial infarction. 32,33 Furthermore, in the HFpEF setting, Przewlocka-Kosmala et al demonstrated that GCW is a better determinant of exercise capacity than GLS and that improvement in functional capacity during follow-up is associated with increment of GCW. 34 Using longitudinal MW analyses, the current study is the first to point out at the role of MW in the risk stratification of HFpEF patients and its association with clinical outcomes.…”
Section: Myocardial Work and Clinical Implications In Heart Failure W...mentioning
confidence: 99%
“…P2: Compared to B1, the area of the red segment of bull's-eye was found to be reduced while the corresponding GLS and GWE were shown to be improved in the B2 (B1, BP 172/92 mmHg; B2, BP 135/80 mmHg) elevated in both Stage 1 and Stage 2 hypertension. 27 Furthermore,…”
Section: Discussionmentioning
confidence: 99%
“…Chan J et al first investigated myocardial work analysis in hypertensive patients and found that GWIand GCW were comparable in patients with stage 1 hypertension and normotensive control subjects, but significantly increased in patients with stage 2 and 3 hypertension [ 76 ], though GWW and GWE remained similar among all groups. Jaglan A et al, on the other hand, found a significant increase in GWW in addition to the similar significant differences in GWI and GCW in patients with stage 1 and 2 hypertension and normotensive subjects [ 77 ]. Nonetheless, it should be noted that the global longitudinal strain in these studies were all comparable between groups, suggesting that these patients were in the early stage of cardiac remodeling and dysfunction.…”
Section: Cardiac Myocardial Work Evaluationmentioning
confidence: 96%